A Circular Approach to Upgrade Cement-based CO2 and Renewable H2: Techno-economic Analysis of SNG Production - Dimitris Ipsakis (AIDIC Servizi S.r.l., 2021)
The present work introduces a feasible, carbon-free integrated process that is based on the catalytic hydrogenation of industrially captured CO2 via green H2 towards the production of synthetic natural gas (SNG). Overall, three systems are being assessed from an economic point of view (sizing and simulation through Aspen Plus and HOMER software): a) H2 production through a combination of renewable energy sources (RES) and water electrolysis, b) cement-based CO2 capture through amines in a continuous absorption/regeneration cycle and c) CO2 catalytic hydrogenation. The basis for the process simulation and the subsequent economic analysis lies on the exploitation of 1,400 kt/y CO2 that are emitted from a typical cement industrial plant. According to this capacity, the integrated system is assessed for a yearly SNG production rate of ~500 kt/y. As was derived from the screening of different market exploitation scenarios (e.g., funding options, increase of CO2 tariffs), a sustainable and feasible solution can be achieved (based on current market values), as long as the RES-H2 system is funded by up to ~35 % or CO2 penalty costs reach levels of >140 €/t in the near future.